Litigation services handbook the role of the financial expert - Weil, Roman L.; Lentz, Daniel G.; Hoffman, David P. (Wiley, 2012)
"A comprehensive reference for financial experts engaged in litigation services, the lawyers who engage them, and the litigants who ultimately benefit from the efforts of both groups, Litigation Services Handbook, Fifth Edition is referred to as the litigation "bible." With nearly fifty chapters reading like a who's who in law and accounting, the handbook includes all aspects of litigation services, including current environments, the process itself, a wealth of cases, how to prove damages, and practical considerations of court appearances"--